Pakistan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper on Pakistan reports that fiscal adjustment, supported by official and private inflows and debt relief, has led to a substantial improvement in public and external debt indicators. International reserves have recovered close to USD 10 billion. Financial sector reforms have resulted in a healthy banking system. With these achievements, vulnerabilities have been greatly reduced, and Pakistan's prospects look favorable. A continuation of prudent fiscal policies, as anchored by the financial responsibility law, is needed to ensure that debt ratios continue on their downward trajectory.